2016
DOI: 10.1021/acsami.6b11462
|View full text |Cite
|
Sign up to set email alerts
|

Optical Devices Constructed from Ferrocene-Modified Microgels for H2O2 Sensing

Abstract: Ferrocene-modified poly(N-isopropylacrylamide)-based microgels were synthesized, characterized, and used to construct optical devices (etalons). The response of the microgels and etalons to HO was investigated, and we show that both the microgel diameter and the optical properties of the etalons depend on the solution concentration of HO from 0.6 to 35 mM. This behavior is a direct result of the oxidation of ferrocene, which influences the microgel diameter. This was also demonstrated by electrochemical-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…The more complex situation is seen when a biocatalyst is introduced into the polymer layer and after the electrocatalytic process it must be regenerated. If the enzyme was placed deep in the layer, the shrinking process would depress the electrocatalysis [26][27][28]. In our case the enzyme was bound to the carboxylic groups after the formation of the gel microparticles, therefore it could not penetrate deeply the microgel particles and was located rather close to the surface.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The more complex situation is seen when a biocatalyst is introduced into the polymer layer and after the electrocatalytic process it must be regenerated. If the enzyme was placed deep in the layer, the shrinking process would depress the electrocatalysis [26][27][28]. In our case the enzyme was bound to the carboxylic groups after the formation of the gel microparticles, therefore it could not penetrate deeply the microgel particles and was located rather close to the surface.…”
Section: Resultsmentioning
confidence: 96%
“…In the simplest cases the electroactive species find it harder to penetrate the shrunken polymer layer and to reach the electrode surface. If the enzyme was placed deep in the layer, the shrinking process would depress the electrocatalysis [26][27][28]. A more complicated situation takes place when the polymer layer contains catalytic centers (organic or inorganic).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we observed a change in the intensity of the reectance peaks in response to H 2 O 2 , which is not typically observed from the microgel-based etalons. 4,49 AgNPs are also well known to absorb visible light due to the excitation of plasmons. 50 With the etalons here, we also found that the intensity of reected light increased from 75% to 120%, possibly due to the reduction of AgNP light absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Photonic crystals have attracted considerable interest due to their low cost, ease of signal readout, simple operation, and their ability to be modied to detect multiple analytes. [1][2][3][4] The Serpe Group pioneered the development of poly(N-isopropylacrylamide) (pNIPAm) microgel-based etalons in 2010. 5,6 Since then, they have been shown to exhibit visual color that can be made to depend on the presence of certain species, or the state of a system, e.g., temperature, pH, 7 Cu 2+ , 8 CO 2 , 9 H 2 O 2 , 4 proteins, 10 and DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation